PENEGAKAN HUKUM TERHADAP PEREDARAN ROKOK TANPA CUKAI OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI (KPPBC) TIPE MADYA PABEAN C BENGKALIS - Naldi, Syafri; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Bengkalis Regency is an archipelago surrounded by strait in Riau Province. To go to Bengkalis Island by land there is only one alternative via Roro crossing. So it becomes one of the most strategic places to smuggle cigarettes and liquor, because this archipelago area is a crossing route that makes it easy for large and small ships to carry out smuggling, while sea transportation via standard Ferry at the official jetty and pompong through illegal ports . The purpose of writing this thesis, namely: First, to find out the law enforcement of the Circulation of Cigarettes Without Excise By the Office of Supervision and Service of Customs and Excise (KPPBC) Type of Customs C Bengkalis. Second, to find out the obstacles and efforts in Law Enforcement on the Circulation of Cigarettes without Excise by the Office of Supervision and Service of Customs and Excise (KPPBC) Type C Customs Bengkalis.This type of research can be classified as a type of sociological legal research, because in this study the authors directly conduct research at the location or places that are examined to provide a complete and clear picture of the problem under study. This research was conducted at the Office of Supervision and Service of Customs and Excise (KPPBC) Type C Customs Bengkalis, while the population and the sample are all parts related to this study, the data sources used, among others, primary data, secondary data, and tertiary data Data collection techniques, namely by interviewing and studying literature.From the results of research and discussion, it can be concluded that, First, the law enforcement conducted by Bengkalis Regency Customs and Excise in eradicating illegal cigarettes without excise in the form of preventive and preventive law enforcement. The two obstacles that arise are the lack of public awareness of illegal cigarettes, the still weak supervision and action carried out by the relevant authorities, and the lack of awareness of cigarette producers in producing illegal cigarettes. The efforts in obstruction of law enforcement against the circulation of illegal cigarettes without excise include raising awareness and legal compliance for the realization of legal effectiveness, and increasing supervision in every port in Bengkalis Regency.Keywords: Circulation-Cigarette-No-Excise.